Fatty Acid Profile of Neutral and Polar Lipid Fraction of Wild Eggs and Hatchlings from Wild and Captive Reared Broodstock of Octopus vulgaris - Estefanell, Juan; Mesa-Rodríguez, Antonio; Ramírez, Besay; La Barbera, Antonio; Socorro, Juan; Hernandez-Cruz, Carmen María; Izquierdo, María Soledad (Frontiers in Physiology, 2017)
The culture of Octopus vulgaris is constrained by unsolved problems in paralarvae rearing, mainly associated to the unknown nutritional requirements of this species in early stages. In this article we studied the fatty acid profile (total, neutral and polar lipid fractions) in wild eggs (N=3) and wild hatchlings (N=3), collected in Gran Canaria (SW) (Spain) with artificial dens, in comparison to hatchlings obtained in captivity (N=3) from broodstock fed on trash fish species. Total lipids were 11.5-13.5% dw, with the polar fraction representing a 70.6-75.5% of total lipid, with lower values in wild hatchling in comparison with captive ones. Docosahexaenoic acid (DHA) was the main component in neutral and polar fatty acid profile in all samples, underlying its importance in this species. Decreasing levels of saturates and arachidonic acid (ARA) from wild eggs to hatchlings, mainly associated to the polar fraction, suggest their use during embryonic development. In hatchlings, increasing levels of oleic acid in the neutral fraction and eicosapentaenoic acid (EPA) in the polar fraction, suggests their importance in hatchlings quality. Wild hatchlings showed in the polar fraction higher oleic acid and ARA, and lower DHA/ARA and EPA/ARA ratios in comparison with captive hatchlings, suggesting a difference in paralarvae nutritional status. These results suggest the importance of n-3 highly unsaturated fatty acids (HUFA), oleic acid and ARA, presented in the adequate lipid fraction, in the diet of broodstock and paralarvae of O. vulgaris.